Design of an Online Brain-Computer Interface System Based on Field Programmable Gate Array - Feng, Zhengquan; Zeng, Lin; Wu, Haijing; Tian, Fengchun; He, Qinghua (Journal of physics. Conference series, 2020)
In the article, an online brain-computer interface (BCI) demo system based on Field Programmable Gate Array (FPGA) was designed. A colour visual stimulator based on a Video Graphics Array (VGA) monitor controlled by FPGA is designed to produce transient visual stimulations. An electroencephalography (EEG) acquisition module including active electrodes and driven-right-leg circuit is used to acquire the visual evoked potential (VEP) signal; Finite impulse response (FIR) filtering combined with an averaging method allows for extraction of the weak VEP signals. The template matching method is used in target identification. The FPGA is successfully used in the BCI system to complete multiple tasks such as the VGA controller, analog to digital (AD) converter controller, VEP signal processor and electronic device controller. Experiments show that the subjects' transient VEP can successfully activate the electronic devices by the online BCI system which has relatively high identification accuracy. All these results show that the real time BCI demo system based on FPGA is feasible and effective.